Pulmonary Thrombosis: A Clinical Pathological Entity Distinct from Pulmonary Embolism? - Marongiu, Francesco; Mameli, Antonella; Grandone, Elvira; Barcellona, Doris (Seminars in Thrombosis and Hemostasis, 2019)
Since Virchow's autopsy studies in the mid-1800s, it has generally been believed that pulmonary embolism (PE) originated from the embolization of fibrin fragments from a deep venous thrombosis (DVT). However, a DVT is often not found in patients with PE (up to 50% of cases). Could fibrin form in the pulmonary vessels without coming from the periphery? In this review, the authors will try to support the hypothesis that a pulmonary thrombosis (PT) may develop. They will do so through different clinical models related to some pathological conditions such as pneumonia, chronic obstructive pulmonary disease (COPD), and asthma, all of which show a close relationship between local inflammation and activation of blood coagulation, two defensive systems that may lead to fibrin deposition in the lungs, thus recognizing the possibility that PT may be a newly recognized entity. An increased risk for PE has been demonstrated in these conditions. Sickle cell disease and assisted reproductive technologies are other very different conditions in which an increased risk for PE has been found. Gaucher's disease is a rare hereditary condition in which the hemostatic system could have a role in the pathogenesis of pulmonary hypertension, which complicates the course of the disease. In particular, the increased risk for PT, common to all these conditions, deserves attention when a patient presents with sudden dyspnea, an unexpected COPD exacerbation, or severe sudden asthmatic dyspnea. As a consequence, prediction scores for venous thromboembolism could be revised.
Keywords: pulmonary embolism; pulmonary thrombosis; pneumonia; chronic obstructive pulmonary disease; asthma; sickle cell disease; Gaucher's disease